Glacial landforms and late Cenozoic history of the weatern Sor-Rondane Mountains - Kiichi Moriwaki; Kazuomi Hirakawa (National Institute of Polar Research, 1992)
The western Sor-Rondane Mountains with the exception of several high peaks were once covered by the ice sheet. The mountains are in some places covered with tills weathered in various degrees. Heavily weathered ground including Pliocene till is found on flat-topped surfaces of the mountains and glacial benches about 100m higher than the present ice surface. Heavily weathered ground is found also in an ice-free valley, bottom of which is lower than surrounding ice surface. Tills of the early to middle Pleistocene are small in quantity, and form only small lateral moraines on the mountain flanks about 100m higher than the present ice surface. Since the late Pleistocene, supraglacial tills have formed moraine fields around the mountains less than 10m above the present ice surface. The Pliocene temperate ice sheet produced, transported and deposited a large quantity of tills, and eroded the valley systems dividing the mountains into several blocks. The ice sheet shrank and most part of the mountains emerged from ice by the latest Pliocene. The lowest level of the ice sheet during this deglaciation was probably lower than that of the present day. The temperate ice sheet changed into cold one probably in early Pleistocene, and re-advanced up to about 100m higher than the present ice surface. Subsequently, the ice sheet retreated again to about 10m higher than the present level by several tens of thousand years ago. Then, notable fluctuation of the ice level has not occurred. The occurrence of a warmer environment is suggested by large crystals of gypsum grown in lakes during the last deglaciation period, though it is not clear whether the ice surface was lower than the present.